Two case reports of right atrial aneurysm. Issue 16 (April 2020) - Li, Hao-Peng; Ye, Xian-Wang; Wang, Hai-Tao
Abstract: Introduction: Right atrial aneurysm (RAA) is a rare congenital heart disease (CHD) that usually shows no symptom and is discovered occasionally. This paper introduces the clinical and imaging data obtained in 2 RAA patients and presents a related literature review with the aim of increasing understanding of this disease. Patient focus: One case showed chest distress, while the other showed symptoms on physical examination and positive signs. Diagnosis: Both of these 2 cases were diagnosed with RAA based on ultrasonography, computed tomography angiography (CTA), and enhanced magnetic resonance imaging (MRI) examinations. Interventions: One patient was orally administered warfarin anticoagulant therapy, while the other was given amiodarone to control arrhythmia as well as warfarin anticoagulant therapy. Results: The clinical symptoms of both cases were not aggravated. Conclusions: RAA is a rare cardiac anomaly that can induce severe complications, and it is mainly diagnosed based on imaging examinations. Conservative treatment and regular imaging monitoring are recommended for asymptomatic patients with no high-risk factors, while surgical treatment should be performed in symptomatic patients with high-risk factors.